Measuring p and s wave velocities of unsaturated soils - Cheng, Zhuoyuan. (2011)
The propagation of Primary (P) and Secondary (S) waves has garnered increasing interest due to its applicability in areas such as geo-prospecting, site investigation and the determination of geo-material properties like degree of saturation (Sr) and stiffness. In this project, the effect of frequency on P and S wave velocities and the relationship of P wave velocity with degree of saturation are investigated. This report consists of both experimental and modeling aspects.The experimental aspect attempts to understand the propagation of P and S waves. The effect of